Conversion of glucose into 5-hydroxymethylfurfural catalyzed by Cr-and Fe-containing mixed-metal metal–organic frameworks. (1st February 2023) - Lu, Chenxi; Zhou, Yuanzhuo; Li, Liangzhi; Chen, Hongwei; Yan, Lishi
Graphical abstract: Highlights: First report of glucose to 5-HMF by Cr-and Fe-containing Mixed-Metal MOFs. Mixed-Metal MOFs were superior to single-metal MOFs and MOFs-SO3 H to generate 5-HMF. Mixed-Metal MOFs had synergistic effect with enhanced acidity for 5-HMF production. Mixed-Metal MOFs showed increased pore size and improved thermal stability. An efficient Mixed-Metal strategy on MOFs catalysts to improve 5-HMF production. Abstract: Catalytic production of 5-hydroxymethylfurfural (5-HMF) from glucose is a promising routine for generation of varied value-added chemicals. Herein, Mixed-Metal metal–organic frameworks (MOFs)–Fe/MIL-101(Cr) and MIL-101(Cr, Fe) obtained from post-synthesis modification and one-pot synthesis approach respectively were applied for catalytic converting glucose to 5-HMF. The synthesized Mixed-Metal MOFs were characterized by PXRD, SEM, N2 adsorption–desorption analysis, TGA, XPS and NH3 -TPD. Cr-and Fe-containing Mixed-Metal MOFs Fe/MIL-101(Cr) and MIL-101(Cr, Fe) presented synergistic effect with enhanced catalytic ability for glucose transformation to 5-HMF compared with typical single-metal MOFs and sulfonic acid-functionalized MOFs. Moreover, these two Mixed-Metal MOFs also presented better thermal stability than single-metal MOFs like MIL-101(Cr). Fe/MIL-101(Cr) was found to possess higher catalytic performance than MIL-101(Cr, Fe). 55.8 % 5-HMF yield was obtained with Fe/MIL-101(Cr) at 170 °C for 2 h in DMSO/water system. In addition, Fe/MIL-101(Cr) demonstrated desired recyclability for five times without incredible loss in its activity. This study provides a Mixed-Metal strategy on MOFs for improving catalytic efficiency of glucose conversion to 5-HMF.